2018
DOI: 10.1016/j.neuroimage.2017.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the hippocampus: An intrinsic coordinate system for subfield segmentations and quantitative mapping

Abstract: The hippocampus, like the neocortex, has a morphological structure that is complex and variable in its folding pattern, especially in the hippocampal head. The current study presents a computational method to unfold hippocampal grey matter, with a particular focus on the hippocampal head where complexity is highest due to medial curving of the structure and the variable presence of digitations. This unfolding was performed on segmentations from high-resolution, T2-weighted 7T MRI data from 12 healthy participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 36 publications
8
103
0
Order By: Relevance
“…These features are illustrated at the top of the figure, but additional details can be found in the Materials and Methods section. As in related work (Duvernoy et al, 2013;DeKraker et al, 2018), thickness was highest in the subiculum and CA4 and lowest in CA2. Curvature was generally high in subiculum, which reflects its outward curling away from the rest of the hippocampus, but in CA1 vertical bands of positive and negative values can be seen which correspond to the hippocampal gyrifications seen in Figure 1.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…These features are illustrated at the top of the figure, but additional details can be found in the Materials and Methods section. As in related work (Duvernoy et al, 2013;DeKraker et al, 2018), thickness was highest in the subiculum and CA4 and lowest in CA2. Curvature was generally high in subiculum, which reflects its outward curling away from the rest of the hippocampus, but in CA1 vertical bands of positive and negative values can be seen which correspond to the hippocampal gyrifications seen in Figure 1.…”
Section: Resultssupporting
confidence: 74%
“…This lack of detail would also lead to overinflated thickness measures, larger overall volumes, and perhaps differences in the proportional sizes of some subfields along the anterior-posterior extent of the hippocampus. Quantitative MR, such as T1 mapping, may additionally provide cues to approximate cytoarchitectonic features and indeed in our previous work we observed higher T1-weights in CA2 and CA3 (DeKraker et al, 2018) which may be driven by higher neuronal cell densities as observed in the current study. Thus the features described here show clear promise for characterizing or segmenting the hippocampus in future MRI work.…”
Section: Structural Characterization Of the Hippocampus In Bigbrainsupporting
confidence: 84%
See 3 more Smart Citations